Laterality of lower limbs in cross country skiing and on rollerskis - Charousek, J.; Jandova, S.; Curikova, L. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Laterality affects human movements. The influence of lateral preference on the quality of sport and basic movements has been investigated in several papers (e.g. Vaverka, 2005). One of the continuously discussed problems in cross country skiing is the pressure distribution during skating (Rapp et al., 2009 and others). The aim of this study was to analyse the pressure distribution between the feet and the boot during V2 skating depending on the preference of lower limbs.